Analisis Kestabilan Lereng Jalan Tambang Menggunakan Metode Bishop Simplied Di Area Penambangan Bijih Besi PT.Aro Suka Mandiri, Provinsi Sumatera Barat. - TAUFAN PRAYOGI; Yoszi Mingsi Anaperta (Departemen Teknik Pertambangan FT UNP, 2021)
PT. Aro Suka Mandiri is a company engaged in the mining of Iron Ore which is located in Batang Pamo Village, IX Koto District, Sungai Lasi, Solok Regency, West Sumatra Province. PT. Aro Suka Mandiri made roads on the hillside by dividing the ridge using an excavator. The actual geometry in the field has an overal slop slope height of 21.497 m with a slope of 68 ° and the actual slope FK value in saturated conditions is 0.962. With the slope and steep road heights as well as the maximum range of excavator digging length, it is not efficient to carry out a road construction system on a slope with a single slope design. This study aims to plan the geometry of the overal slope to obtain a safe slope FK value of 1.3 This research was conducted using the bishop method to obtain the FK value of the overal slope slopes. The actual slope geometry was changed, for the overall slope height of 21.497 m with an angle of 58˚ so that the FK value was 1.325. Furthermore, the slope modification is carried out by making a bend on the slope using the bishop method and the FK value for the overall slope in saturated conditions is 1.316. From the data analysis, the results obtained for single slope 1 with a height of 10.008 obtained FK in a saturated condition of 1,701, while for single slope 2 a height of 11.489 obtained FK in a saturated condition of 2,176. So it can be concluded that after redesigning the slope geometry using the bishop method the slope can be stated in a safe condition. Keywords: initial geometry, simplified bishop, simplified janbu, safety factor